2014
DOI: 10.1021/am503878d
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Printing Fiber Reinforced Hydrogel Composites

Abstract: An additive manufacturing process that combines digital modeling and 3D printing was used to prepare fiber reinforced hydrogels in a single-step process. The composite materials were fabricated by selectively pattering a combination of alginate/acrylamide gel precursor solution and an epoxy based UV-curable adhesive (Emax 904 Gel-SC) with an extrusion printer. UV irradiation was used to cure the two inks into a single composite material. Spatial control of fiber distribution within the digital models allowed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
118
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 172 publications
(119 citation statements)
references
References 24 publications
1
118
0
Order By: Relevance
“…Improved mechanical properties Cartilage [95] Anisotropic filler DIW PEGDA, alginate, gelatin Laponite RD, Laponite XLG Improved selfsupporting capacity and young's modulus General [96] 3D plotting N-acryloyl glycinamide Laponite XLG Improved tensile and compression properties and biological properties Bone [97] 3D plotting Alginatemethylcellulose Laponite…”
Section: Improved Radiopacitymentioning
confidence: 99%
See 2 more Smart Citations
“…Improved mechanical properties Cartilage [95] Anisotropic filler DIW PEGDA, alginate, gelatin Laponite RD, Laponite XLG Improved selfsupporting capacity and young's modulus General [96] 3D plotting N-acryloyl glycinamide Laponite XLG Improved tensile and compression properties and biological properties Bone [97] 3D plotting Alginatemethylcellulose Laponite…”
Section: Improved Radiopacitymentioning
confidence: 99%
“…Fiber reinforcements can also improve mechanical properties of hydrogel matrix in which the fiber contents and its distribution inside its matrix determine mechanical properties such as stiffness and strength of composites [92][93][94][95] . In the case of common 3D printing systems, short fiber reinforcements are the most commonly used due to its easy processing procedure at low cost.…”
Section: Fiber-reinforced Hydrogel Composites 3d Printingmentioning
confidence: 99%
See 1 more Smart Citation
“…These two inks can be incorporated into the one printing process because they have similar rheological properties, are both cured by UV initiated free radical polymerization reaction and display strong adhesion. [5] Adhesion between materials is important when forming composites for transferring stresses from the matrix onto the reinforcing phase. Adhesion is also important when fabricating multi-component devices as interfaces can act as a point of weakness in the devices structure.…”
Section: Adhesion Testingmentioning
confidence: 99%
“…Tensile testing of the printed materials has shown that composites with higher volume fractions of Emax fibers display greater tensile strength and modulus. [5] The versatility of digital modeling enables these composites to be fabricated directly into complex shapes and useful structures. Figure 1e.…”
Section: Adhesion Testingmentioning
confidence: 99%